HOME RANGE AND MOVEMENTS OF WILD TURKEYS – A REVIEW - Edward K. Brown (Wildlife Society Bulletin)
Abstract Home range is defined and information presented on methods of collecting data and computing home range of wild turkeys, on distances traveled and dispersal from managed areas, and on the variability of factors influencing the measurement of home range. Reported annual ranges of wild turkeys varied from 140 ha in Alabama to 553 ha in Missouri; seasonal ranges varied from a spring range of 95 ha in South Carolina to a winter range of 683 ha in Michigan. Linear distances traveled for wild turkeys ranged from 1.5 km in Virginia to 20.1 km in Texas.